Molecular and biological characterization of an isolate of the potyvirus passiflora virus Y naturally infecting soybean (Glycine max) in Brazil - Ribeiro-Junior, Marcos Roberto [UNESP]; Barreto da Silva, Felipe [UNESP]; Marubayashi, Julio Massaharu [UNESP]; Uzan, Juliana [UNESP]; Nogueira, Angelica Maria [UNESP]; Muller, Cristiane; Nascimento, Daniele Maria; Yuki, Valdir Atsushi; Narita, Nobuyoshi; Pavan, Marcelo Agenor [UNESP]; Ochoa-Corona, Francisco Manuel; Krause-Sakate, Renate [UNESP] (Springer Nature, 2022)
Passiflora virus Y was detected naturally infecting soybean (Glycine max) for the first time in Brazil. Here, we report the nearly complete genome sequence and molecular and biological properties of the PaVY-Br isolate. The nearly complete genome sequence is 9679 nt long and shares 84.4% nt sequence identity with a previously reported PaVY isolate from Passiflora sp. PaVY-Br induced chlorotic spots and systemic mosaic on soybean and chlorotic local lesions on yellow passion fruit (Passiflora edulis) and sesame (Sesamum indicum). The virus was successfully transmitted by Myzus persicae, indicating that this aphid vector can contribute to the spread of PaYV from passion fruit to soybean plants. Additional epidemiological research is in progress to investigate the distribution of PaVY in soybean production areas in Brazil.